Parent-Conducted Competing Stimulus Assessment and Treatment of Challenging Behavior by a Girl With Kleefstra Syndrome. Issue 4 (2nd October 2022) - Thomas, Benjamin R.; White, Kaliah M.; Clayborne, Joy C.; O'Connor, Julia T.
Abstract: Challenging behaviors maintained by sensory consequences (i.e., automatic reinforcement) can be difficult to treat without constant supervision. This type of time commitment can be extremely difficult for families to do effectively. Competing stimulus-based treatments have shown promise for treating challenging behavior during periods of low supervision as they require minimal interaction with the child. Accordingly, families may benefit from learning to become self-sufficient in using this approach to assessment and treatment. This study evaluated the effects of a parent-conducted assessment and treatment on the challenging behavior of destructive paper tearing by a girl with Kleefstra Syndrome (9q34.3 deletion syndrome). Following a parent-conducted functional analysis, the mother completed an abbreviated competing stimulus assessment (CSA), and then delivered a treatment involving concurrent availability of all items identified in her daughter's CSA. Results showed that the treatment was associated with generalized, reduction in challenging behavior that maintained in follow-up.